PHARMACOLOGICAL ASSESSMENT OF MOBILE RADIATION IMPACT ON VILDAGLIPTIN EFFICACY IN ALLOXAN-INDUCED DIABETIC RODENTS - ABHISHEK MORE; MUKESH MOHITE (The Bioscan, 2025)
The widespread usage of cell phones has sparked worries about how electromagnetic radiation (EMR) may affect the pharmacological effectiveness of medicinal substances. Vildagliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor that is commonly used to treat type 2 diabetes mellitus. The current study assessed the impact of mobile phone radiation, particularly when using Bluetooth and Flight modes, on the drug's chemical stability and antidiabetic effectiveness. EMR-exposed and non-exposed vildagliptin were given to alloxan-induced diabetic Wistar rats for pharmacological evaluation. Variations in the glucose-lowering efficacy were assessed by tracking changes in fasting blood glucose levels. Significant alterations in the drug's distinctive functional groups (FTIR) and thermal behaviour (DSC) were brought about by exposure to EMR, especially in Bluetooth mode. Additionally, the active drug content (HPLC) decreased. The hypoglycaemic response in diabetic rats was significantly attenuated in correlation with these chemical alterations, suggesting a possible loss of therapeutic efficacy. The results highlight the necessity of strict handling and storage procedures to maintain the stability and effectiveness of pharmaceutical products by indicating that electromagnetic radiation may jeopardize vildagliptin's pharmacodynamic activity as well as its chemical integrity.